Nonlinear decay of high-power microwaves into trapped modes in inhomogeneous plasma. (1st July 2022) - Tancetti, A.; Nielsen, S.K.; Rasmussen, J.; Gusakov, E.Z.; Popov, A.Yu.; Moseev, D.; Stange, T.; Senstius, M.G.; Killer, C.; Vecséi, M.; Jensen, T.; Zanini, M.; et al.
Abstract: We present novel experimental evidence of parametric decay instability of microwave beams in the plasma edge of the Wendelstein 7-X stellarator. We propose that the instability is sustained by trapping of only one daughter wave in the non-monotonic density profile measured with high spatial resolution within a stationary magnetic island. The power levels and spectral shapes of the detected microwave signal are reproduced by numerical modelling and a theoretical power threshold is predicted around 300 kW, comparable with observations. We predict a fraction of power drained by daughter waves around 4% in the experiments, potentially increasing above 50% for more hollow edge density profiles. Such absorption levels could significantly reduce the efficiency of the microwave heating and current-drive system in tokamaks and stellarators.